Research on the Development Efficiency of Leisure Agriculture in Hebei Province under the Background of Rural Revitalization - Yuan, Jiawei; Zhang, Shiyue; Zhang, Siqi; Lv, Yahui (Journal of Educational Research and Policies, 2024)
Objective: To explore the static and dynamic characteristics of the development efficiency of leisure agriculture in Hebei Province after the implementation of the rural revitalization strategy. Methods: First, the study constructed an efficiency evaluation system including input indicators such as leisure agriculture area, total investment, and number of employees, as well as output indicators such as business income, reception, and number of farmers driven by data envelopment analysis (DEA). Then, the static and dynamic empirical analysis of the development efficiency of leisure agriculture was carried out using relevant data from 11 prefecture-level cities in Hebei Province. Conclusions: 1) In 2020, the comprehensive efficiency of leisure agriculture in Hebei Province has not yet reached the optimal level. There are deficiencies in resource allocation, industrial scale, and quality of employees. There is a large room for improvement in pure technical efficiency and scale efficiency. 2) Dynamic analysis shows that the average total factor productivity index of leisure agriculture in Hebei Province from 2018 to 2020 was 1.091, showing an overall upward trend. Technological progress is the key factor to promote development. Therefore, this article believes that in order to further play the role of leisure agriculture in rural revitalization, it is necessary to promote its economies of scale and strengthen scientific and technological empowerment with the help of digital rural construction.